2021
DOI: 10.35371/aoem.2021.33.e9
|View full text |Cite
|
Sign up to set email alerts
|

The association between non-regular work patterns and insomnia among Korean wage workers: the fifth Korean working condition survey

Abstract: Background Non-regular workers are steadily increasing on account of improving corporate productivity. They are classified as non-permanent, part-time, or non-typical workers. Non-regular work has a negative impact on workers' physical and mental health. This study analyzed the relationship between non-permanent, part-time and non-typical work and insomnia among Korean wage workers, and investigated the differences and interactions between different work patterns. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Second, although the data collection was based on the panel participants randomly selected, the sample estimate has a limitation in its lack of being reflective of the actual conditions of all workers in the country. For example, the percentage of wage workers aged 20–29, 30–39, 40–49, 50–59 and 60 years were 13.1%, 23.9%, 26.4%, 22.7% and 13.9%, respectively, in the nationally representative survey in South Korea [ 36 , 37 ], but our data were obtained from a higher proportion of younger workers. However, we believe that the important health conditions suggested by our study are of significant importance for the entire working population in South Korea.…”
Section: Discussionmentioning
confidence: 98%
“…Second, although the data collection was based on the panel participants randomly selected, the sample estimate has a limitation in its lack of being reflective of the actual conditions of all workers in the country. For example, the percentage of wage workers aged 20–29, 30–39, 40–49, 50–59 and 60 years were 13.1%, 23.9%, 26.4%, 22.7% and 13.9%, respectively, in the nationally representative survey in South Korea [ 36 , 37 ], but our data were obtained from a higher proportion of younger workers. However, we believe that the important health conditions suggested by our study are of significant importance for the entire working population in South Korea.…”
Section: Discussionmentioning
confidence: 98%
“…The negative perception of one’s job security and prospects could spill over to the home domain, impairing the quality of rest and sleep [ 39 ]. From this perspective, some studies have found detrimental effects of job insecurity on workers’ sleep quality in both Western and Asian countries [ 29 , 40 ].…”
Section: Discussionmentioning
confidence: 99%